2019
DOI: 10.1002/jper.19-0310
|View full text |Cite
|
Sign up to set email alerts
|

The significance of surgically modifying soft tissue phenotype around fixed dental prostheses: An American Academy of Periodontology best evidence review

Abstract: Background This systematic review endeavored to investigate the effect of soft tissue phenotype modification therapy (PhMT‐s) at sites with a tooth or an implant supported fixed dental prosthesis. Methods A comprehensive literature search was conducted by two independent examiners to identify relevant studies reporting differences in clinical, esthetic, or radiographic outcomes of interest between sites underwent PhMT‐s and sites that remained untreated. Risk of bias assessment was calculated for all included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 91 publications
2
22
1
Order By: Relevance
“…9,18 Additional horizontal and vertical soft tissue augmentation for peri-implant phenotype modification may contribute to boost the esthetic outcomes. 19,20 Whether immediate or delayed, implant placement in an unfavorable position can also influence the esthetic outcomes of tooth replacement therapy. Inaccurate implant placement can lead to the occurrence of distal papilla deficiency because of, for example, an excessively deep position of the restorative platform, which may induce severe saucerization and extensive peri-implant bone remodeling, and/or close proximity to the lateral incisor.…”
Section: Surgical Managementmentioning
confidence: 99%
“…9,18 Additional horizontal and vertical soft tissue augmentation for peri-implant phenotype modification may contribute to boost the esthetic outcomes. 19,20 Whether immediate or delayed, implant placement in an unfavorable position can also influence the esthetic outcomes of tooth replacement therapy. Inaccurate implant placement can lead to the occurrence of distal papilla deficiency because of, for example, an excessively deep position of the restorative platform, which may induce severe saucerization and extensive peri-implant bone remodeling, and/or close proximity to the lateral incisor.…”
Section: Surgical Managementmentioning
confidence: 99%
“…It has been suggested that the thin tissue phenotype around dental implants is at a higher risk for increased inflammation. 5,7 This may be due to plaque accumulation resulting in a biofilm that can cause ‡ Gem-21S, Lynch Biologics, Franklin, TN † Gore-Tex Suture, W.L. Gore & Associates, Flagstaff, AZ ‡ NobelActive Parallel Wall, Nobel Biocare, Yorba Linda, CA § Smart Peg, Osstell, Cumberland, MD inflammation.…”
Section: Clinical Presentation Case Management and Clinical Outcomesmentioning
confidence: 99%
“…However, the presence of keratinized tissue may help reduce a patient's inflammatory response associated with peri-implant mucositis, comfort during mastication, and ease of plaque removal. 5,6 Two dental implant cases are presented where PhMT has been performed in either a reactive or proactive manner involving subepithelial connective tissue grafting to increase periimplant keratinized tissue. The resulting outcome created an improved environment conducive to maintaining long-term peri-implant health and function while also trying to maintain esthetics when PhMT is performed proactively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations